Molecular technique for detection and identification of Helicobacter pylori in clinical specimens: a comparison with the classical diagnostic method - Jéssica C. Nevoa; Roger Luiz Rodrigues; Gabriela L. Menezes; Andressa R. Lopes; Hemelly F. Nascimento; Silvana B. Santiago; Marcos L. Morelli; Monica S. Barbosa
ABSTRACT Introduction: Helicobacter pylori is a bacterium found in human epithelial cells of the gastrointestinal tract. Its infection is related to different diseases, such as chronic gastritis, peptic ulcers, gastric lymphoma and adenocarcinoma. The infection by H. pylori is present in more than a half of the world population. Objectives: To detect H. pylori and to compare the diagnostic methods of the rapid urease test (RUT) and polymerase chain reaction (PCR). Materials and methods: The study was conducted between April and July, 2015. For such, three biopsies were collected from each patient. Two were used for PCR and one for RUT. Results: A total of 85 samples were collected from patients undergoing endoscopy, with 56 (65.88%) females and 29 (34.11%) males. From the total samples subjected to RUT, 15 (17.64%) were positive and 70 (82.35%), negative. In PCR for detection of gene 16S ribosomal ribonucleic acid (rRNA) of H. pylori, 66 (77.64%) presented positive results and 19 (22.35%), negative results. For the analysis of the presence of UreA gene in all samples, positive results were found in 70 (82.35%), and negative in 15 (17.64%). According to the results, RUT and the molecular test presented statistical difference. Conclusion: PCR is a useful method in the laboratorial routine to detect the presence of H. pylori in the stomach tissue, due to high sensitivity and specificity, but it requires a more careful analysis and standardization.